Pragmatics and the invisible language of relationships: the case of Korean and KFL learners - Driggs, D (2023)
This thesis finds itself at the intersection of two fast-moving global trends in linguistics research: first, the swiftly growing interest in pragmatics as a field in need of further development, definition, and delineation between global languages with vastly differing sociocultural patterns of behavior, including politeness (Kiaer (2020b), Taguchi (2019)); and second, unprecedented international attention on the Korean peninsula, leading to a wave of Korean language study by learners of Korean as a foreign language (KFL learners), with steadily increasing enrollment numbers continuing to outperform other languages (Pickles, 2018). These two phenomena have created a specific set of circumstances in which the study of Korean pragmatics and Korean pragmatics education has become extremely relevant. This thesis seeks to address that set of circumstances by setting out, through a variety of ethnographic methodologies, to understand how native Korean speakers perceive their own pragmatic experiences. It then compares Korean speakers’ pragmatic experiences with those of Chinese and Japanese speakers, in order to identify the unique pragmatic features of Korean. Finally, this thesis explores the KFL classroom and examines how KFL learners are currently being exposed to Korean pragmatics in their studies. Through the methodologies pursued here, this thesis finds that Korean speakers are uniquely required by their linguistic circumstances to constantly engage with pragmatic skills, including speech styles and address terms, in order to engage in culturally required relational dynamics, and that KFL learners are being underprepared by current KFL curricula to engage in Korean relational dynamics using those pragmatic skills.